Pengembangan Pembelajaran Qur’an Hadits Dengan Flipped Learning Untuk Siswa Kelas V MI Wali Songo Annur Wadung Tuban - Ali Yusuf; Husniyatus Salamah Zainyati (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Abstract. One of the developments in learning is to improve technology in teaching and learning, one of which is reverse learning. It is an approach in which traditional one-way madrasahs are reversed to make room for active learning opportunities in which educators shift learning to individuals whose learning spaces are facilitated by technology. The purpose of this research is to identify and to obtain information related to the development of student learning in improving student communication and critical thinking skills on the material of the Qur'an hadith with flipped learning. The research used an exploratory case study method and the research approach used qualitative methods used to obtain information on the learning activities of the Al-Qur'an Hadith grade 5.In this study, the respondents were 8 students in grade 5 and 8 parents of Madrasah Ibtidaiyah Wali Songo Annur Wadung students. . The interview was conducted face-to-face because it happened that the student's residence was not far from the Madrasah with a list of questions that had been compiled and developedbased on related literature. The results of this study are that there are several obstacles experienced by students, teachers and parents in teaching and learningactivities, namely the mastery of technology is still lacking, the addition of internet quota costs, unstable networks, the ability of children and parents to operate Hand Phones or Computers. students who have IT, the lack of enthusiasm of parents in accompanying children to learn. Keyword: Flipped Learning, learning, Al-Qur'ah Hadith, Media Video